Opinions on Content That Are Extremely Controversial on the Indonesian Twitter - Nuruzzaman NURUZZAMAN; Ahmad SIHABUDIN; Jamalullail JAMALULLAIL (International Journal of Environmental, Sustainability, and Social Science, 2023)
The influence of media technology extends beyond their importance to human existence, to the point where they are being utilized to disseminate revolutionary propaganda in the form of hate speech. According to McLuhan's idea, for a communication phenomena to occur through the use of media, it must do more than just consider the medium in which the message will be delivered. In analyzing the context of the message on a specific platform, this investigation on Twitter in Indonesia demonstrates how Twitter has become a facilitator of extremism and an accelerant of radicalization chances. In contrast to the common belief that radicalism has a single meaning, the purpose of this study is to explain why the media and messages can only substantially alter the mode of communication if they are backed by ideological components and features of the technology itself in Indonesia. Keywords: Radical Contents, Radicalism, Social media, Digital communication